Krishoker-Hut: a novel approach to empower rural agricultural trade through technology - Nayeem, Md. Hasib Noor; Sipon, Abdullah Al; Rahman, Asfia; Bhowmik, Neeladri; Ahmed, Nafisa (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.